Analysis of Social Emotional Development in Infants Based on Psychological Studies - Muhammad Alfiyansyah; Indah Hari Utami (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The baby's socio-emotional development should be one of the main focuses of parents, because if social-emotional development does not go well it will influence and inhibit other developments such as psychomotor development, affective and other infant development. The baby's socio-emotional development can certainly be seen from a variety of factors and signs such as smiling babies, angry babies, crying are all signs that the child is experiencing social-emotional development. This study uses a library research approach or library research where this research study seeks to examine various books, relevant journals and also news related to the focus of research in this paper. And it can be concluded that the social-emotional development of the baby must be developed in accordance with the development of his age so that it is useful when the baby is growing up can control emotions well and also has a good tolerance and good social. AbstrakPerkembangan Sosial-emosional bayi hendaknya menjadi salah satu fokus utama orang tua, sebab apabila perkembangan sosial-emosional tidak berjalan dengan baik maka akan berpengaruh dan menghambat terhadap perkembangan lainnya seperti perkembangan psikomotorik, afektif dan perkembangan bayi lainnya. Perkembangan sosial-emosional bayi tentu dapat dilihat dari berbagai macam faktor dan tanda-tanda seperti bayi tersenyum, bayi marah, menangis itu semua merupakan tanda bahwasannya anak sedang mengalami perkembangan sosial-emosional. Kajian ini menggunakan pendekatan library research atau penelitian pustaka dimana kajian penilitian ini berusaha mengkaji dari berbagai buku yang terkit, jurnal-jurnal yang relevan dan juga berita-berita yang berkaitan dengan fokus penelitian dalam tulisan ini. Dan dapat disimpulkan bahwasannya perkembangan sosial-emosional bayi harus di kembangkan sesuai dengan perkembangan usianya agar hal tersebut bermanfaat ketika bayi beranjak dewasa dapat mengontrol emosi dengan baik dan juga memiliki tenggang rasa dan sosial yang baik.